Akseptabilitas Terjemahan Kumpulan Cerita Anak Oleh Mahasiswa Bahasa Dan Satra Jawa UNNES - Widihastuti, Rahma Ari (Kamaya: Jurnal Ilmu Agama, 2025)
With the aim of presenting alternative children's stories in Javanese, Javanese Language and Literature students translated children's stories from several stories by Javanese literary writers. The purpose of this study was to analyze the acceptability of students' translation results for children's literature in Javanese. The research method used a qualitative approach, a case study method with translation assessment criteria from Rochayah Machali with four aspects. The data source was the results of student translations consisting of 12 children's stories with various dialects. Data analysis by Cresswell with six stages. The results of the study showed that in the translation results seen from several aspects: 1) the accuracy of meaning production, there were several transpositions because there were adjustments to the TL context, but modulation was not found because the majority of translations were word-by-word, idioms were found in several stories and were correct in their translation, semantic aspects were in accordance with conventions, pragmatic meanings were sequential even though some words did not have equivalents in the TL; 2) reasonableness of expression, some stories were translated naturally, some were still stiff; 3) terminology, it can be said that 70% of the 12 stories used dialect terms correctly and clearly, but the rest were lacking. 4) spelling, the majority of errors in punctuation, typos, and typical Javanese spelling. Based on these results, it was concluded that 8 stories were categorized as good translations (C) and 4 stories were categorized as fair translations (D).